2008
DOI: 10.1186/1475-2875-7-38
|View full text |Cite
|
Sign up to set email alerts
|

An experimental hut evaluation of Olyset® nets against anopheline mosquitoes after seven years use in Tanzanian villages

Abstract: Background: Long-lasting insecticidal nets (LLINs) are advocated by WHO for protection against malaria. Of the three brands of LLINs currently approved by WHO, Olyset ® is the only one currently granted full recommendation. With this type of LLIN, the insecticide (permethrin) is incorporated into the polyethylene fibre during manufacture and diffuses from the core to the surface, thereby maintaining surface concentrations. It has not been determined for how long Olyset nets remain protective against mosquitoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
83
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 13 publications
10
83
0
2
Order By: Relevance
“…gambiae in Cote d'Ivoire (N'Guessan et al 2001). Similar study results have been documented in Tanzania in which washing did not have significant effect on knockdown or mortality of vector mosquitoes (Tami et al 2004, Malima et al 2008). The disease transmission trends were clearly declining, and community acceptance was high and forthcoming reporting relief not only from mosquito bites but also other household pests.…”
Section: Discussionsupporting
confidence: 72%
“…gambiae in Cote d'Ivoire (N'Guessan et al 2001). Similar study results have been documented in Tanzania in which washing did not have significant effect on knockdown or mortality of vector mosquitoes (Tami et al 2004, Malima et al 2008). The disease transmission trends were clearly declining, and community acceptance was high and forthcoming reporting relief not only from mosquito bites but also other household pests.…”
Section: Discussionsupporting
confidence: 72%
“…5 Despite the large investment in the procurement and distribution of ITNs and LLINs, which is estimated to have increased from 6 million US dollars (USD) in 2004 to 92 million in 2011, 4 little information exists on the physical durability of LLINs in the field; and few malaria control programs to date have systematically monitored the performance of LLINs in terms of physical durability after mass distributions. [8][9][10][11][12][13][14][15][16] Several studies provide evidence that the levels of insecticide present in LLINs months and years after their distribution remains adequate 10,[17][18][19][20][21][22][23] ; however, this information alone does not entirely address whether LLINs remain effective as a vector control tool over several years of daily use. The physical integrity of the LLIN, specifically the presence of holes, tears, and repairs, needs to be taken into account when determining whether an LLIN is capable of protecting individuals or communities from mosquitoes infected with malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Each insecticide has a distinct spectrum of insecticidal outcomes on mosquitoes, which imply that LLINs based on different insecticides may have different effects on mosquito vectors. Previous studies have suggested that LLINs elicited very low level of deterrence against susceptible mosquito vectors and were effective because they did not allow mosquitos to feed on the user [19,[21][22][23][24].…”
Section: An Operational Description Of Insecticides Used In Llinsmentioning
confidence: 99%